The political economy of inclusion and exclusion: state, labour and the costs of supply chain integration in the Eastern Caribbean. Issue 3 (4th May 2022) - Fridell, Gavin
Abstract: The dual emphasis on the benefits of global supply chain integration and private governance to address its ethical gaps have given prominence to an inclusive vision of chains which, this paper argues, drawing on the case of St. Vincent and the Grenadines (SVG), has been greatly exaggerated. In the post-war era, SVG built a successful banana industry under a preferential agreement with the EU. When the agreement collapsed under free trade reforms, the burden of finding new forms of reintegration fell on the state and laboring classes. The paper argues that conventional supply chain approaches have adopted a static understanding of the relationship between inclusion and exclusion, overlooking the exclusionary nature of supply chains and placing too much emphasis on assessing the possibilities for private supply chain initiatives to address their negative social and environmental impacts. The effect has been to obscure the centrality of the state and laboring classes in continuing, out of necessity, to confront, manage, and address the many costs that corporations are not willing to pay. It is their centrality to managing the uneven and unpredictable nature of supply chain integration/reintegration, that is often the most hidden of all.